Inclusión educativa en la gestión formativa del talento humano en la unidad educativa “Marco Aurelio Subía-Batalla de Panupali”. Programa de capacitación de adaptaciones curriculares. - Jácome Segovia, Livia Mariana (2016)
This research work about “educational inclusion in the management training of human talent in educational unit Marco Aurelio Subía - Batalla de Panupali. Curricular and adaptations management program”, had as main objective at Curricular and adaptations management program to achieve the institutional performance; to which applied instruments that collated relevant information on the subject as surveys aimed at the members of the educational community of the institution, where it was found shortcomings in the application of educational inclusion, as respondents mostly were unaware the curricular and adaptations to be applied by the class. With this background we can say that the educational inclusion has an educational and social sense that search to offer an integral education with quality to all students, regardless of their personal characteristics, creating schools eliminating all of type of discrimination and barriers to learning; What this research is considered significant, as it allows for administrative staff, teachers, students and parents have the necessary support staff their academic and personal progress ; against these aspects was developed as a proposed solution a training of curricular adaptations with which the institution staff may have a viable support document in its actions and daily practice in which investigated levels contain viable and up-to-date information , that guides the development of the proposed theme.